Recycling and decontamination of organic waste in Ukraine: Current state, technologies and prospects for the biogasindustry - Boyko, Olexandra O.; Boyko, O. O.; Boyko, A. A.; Boyko, O.; Boyko, A.; Бойко, Олександра Олександрівна; Hapich, H. V.; Гапіч, Геннадій Васильович; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; et al. (Oles Honchar Dnipropetrovsk National University, 2024)
Global and regional competition for natural resources, particularly for land and water, food and fodder, takes place in the context of a dire necessity to limit greenhouse gas emissions and is becoming more and more pressing every year. Environmental soundness, sustainability and security are becoming more relevant and are considered as key elements of modern agricultural enterprises' operation. The concept of the coming years in animal husbandry is non-waste production, which consists in the complete recycling of waste, and if it is impossible – in their safe disposal. If the waste cannot be reused or upcycled, such waste should be transformed into energy. The production of biogas and biomethane contributes to solving two global problems: the growing amount of organic waste produced by modern economies and the negative impact of CO2 emissions on climate change and the environment. We considered the social and economic prerequisites developed in the main sectors of contemporary Ukrainian livestock breeding in terms of potential sources of raw materials for biogas production. The main focus of the study is on the elements of greening of national agriculture, production and on the prospects for the development of the biogasindustry in Ukraine. Favourable conditions for the development of biogas technologies have been identified among large producers of livestock products (dairy cattle breeding, swine breeding and poultry farming). In other sectors, opportunities are still limited due to economic, social and legislative difficulties. The paper also analyses the prospects for the use of various means of combating pathogens for the processing and disposal of organic waste. The main role of anaerobic digestion as an alternative method for the inactivation of dangerous pathogens responsible for infectious and parasitic diseases of animals and humans has been determined. Глобальна та регіональна конкуренція за природні ресурси, зокрема за землю та воду, їжу та фураж, відбувається в контексті гострої необхідності обмежити викиди парникових газів і з кожним роком стає дедалі гострішою. Екологічність, стійкість і безпека стають все більш актуальними і вважаються ключовими елементами функціонування сучасних сільськогосподарських підприємств. Концепція найближчих років у тваринництві – безвідходне виробництво, яке полягає в повній переробці відходів, а при неможливості – в їх безпечній утилізації. Якщо відходи не можна повторно використати або переробити, такі відходи мають бути перетворені в енергію. Виробництво біогазу та біометану сприяє вирішенню двох глобальних проблем: зростання кількості органічних відходів, що виробляються сучасною економікою, та негативного впливу викидів CO2 на зміну клімату та навколишнє середовище. Ми розглянули соціально-економічні передумови, що склалися в основних галузях сучасного українського тваринництва з точки зору потенційних джерел сировини для виробництва біогазу. Основна увага дослідження зосереджена на елементах екологізації вітчизняного сільського господарства, виробництва та на перспективах розвитку біогазової галузі в Україні. Визначено сприятливі умови для розвитку біогазових технологій серед великих виробників продукції тваринництва (молочне скотарство, свинарство та птахівництво). В інших секторах можливості все ще обмежені через економічні, соціальні та законодавчі труднощі. У роботі також проаналізовано перспективи використання різних засобів боротьби зі збудниками хвороб для переробки та утилізації органічних відходів. Визначено основну роль анаеробного зброджування як альтернативного методу інактивації небезпечних збудників інфекційних і паразитарних захворювань тварин і людини.
Переробка та знезараження органічних відходів в Україні : Сучасний стан, технології та перспективи біогазової галузі
Бойко Олександра Олександрівна https://orcid.org/0000-0002-7299-9920 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813 Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228
Keywords: pathogen inactivation; інактивація збудника; biogas; біогаз; organic waste processing; переробка органічних відходів; animal husbandry; тваринництво